Chitin and Chitosan - Physicochemical Properties and Industrial Applications [Working Title] 2021
DOI: 10.5772/intechopen.95518
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Solid Dispersion Strategy for Solubility Enhancement of Poorly Soluble Drugs by Co-Milling Technique

Abstract: Amorphous ternary solid dispersion has become one of the strategies commonly used for improving the solubility and bioavailability of poorly water soluble drugs. Such multicomponent solid dispersion can be obtained by different techniques, this chapter provides an overview of ternary solid dispersion by co-milling method from the perspectives of physico-chemical characteristics in vitro and in vivo performance. A considerable improvement of solubility was obtained for many active pharmaceutical ingredients (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…It is a clear possibility that transforming from crystalline state to amorphous state by dry milling can happen [ 60 , 61 ]. Co-milling with PVP is the method of preparing amorphous solid dispersion, and it is expected that there exist no melting peaks in amorphous state.…”
Section: Resultsmentioning
confidence: 99%
“…It is a clear possibility that transforming from crystalline state to amorphous state by dry milling can happen [ 60 , 61 ]. Co-milling with PVP is the method of preparing amorphous solid dispersion, and it is expected that there exist no melting peaks in amorphous state.…”
Section: Resultsmentioning
confidence: 99%
“…of efavirenz was successfully obtained by ternary solid dispersion using PVP and polyethylene glycol 8000 [61]. In addition to aforesaid, we have recently reported that solubility enhancement of poorly soluble drugs can be achieved by co-milling the drug in the presence of multiple carriers, and led to the formation of physically stable amorphous system and was more effective than simple binary systems [62].…”
Section: Dosage Formsmentioning
confidence: 99%
“…Furthermore, the dissolution rate of ibuprofen was significantly increased in the presence of PVP and complexation by βCD. This was due to various mechanisms (intermolecular interactions, carrier synergy, anti-plasticizing effect, increased hydrophilicity, decreased particle size, and accretion to βCD cavities) that promote the stabilization of amorphous ibuprofen under stress conditions [ 120 ].…”
Section: Physical Stabilitymentioning
confidence: 99%